Small Java : - Deitel, H. M. (Prentice Hall, 2005)
This special edition of Java How to Program is up-to-date with the Java 2 Platform Standard Edition 1.5. It covers fundamental programming topics and provides several extra chapters so readers can include or omit material as needed. Includes Recursion and Searching and Sorting chapters. Provides extensive complete programming exercises plus "What does this program do?", "What's wrong with this program?", "Complete the program" and "Modify the program" exercises. Covers text-file processing. Features coverage of special topics, such as pre- and postconditions, invariants, testing and debugging, ethics and software engineering. Includes a CD-ROM with every copy of the book that contains: (subject to change) Java™ 2 Platform, Standard Edition 1.5; Netbeans; JCreator LE; jEdit; jGRASP; BlueJ; Source code for all the book's examples; Hyperlinks to valuable Java™ demos and Internet resources. A useful brief reference for programmers or anyone who wants to learn more about the Java programming language.